(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2007)
A 9-year-old male child presented with fever, polyarthritis, cough and difficult breathing. He had characteristics skin lesion and reticulonodular shadows on chest X-ray. Initially, it appeared to be a case of sarcoidosis but finally histologically proved to be a rare adipose tissue disorder - Weber Christian disease (WCD). (J Bangladesh Coll Phys Surg 2007; 25 : 43-46)